Pendidikan di Era Milenial dan Manajemen Pendidikan di Sekolah - Tripitoyo Tripitoyo; Rusmiyati Rusmiyati; Kabri Kabri; Partono Nyana Suryanadi (Jurnal Budi Pekerti Agama Buddha, 2025)
Buddhist education in the millennial era faces various internal and external challenges, especially in adapting to the character of the younger generation who are highly dependent on information technology but weak in filtering moral values. Buddhist educational institutions also still face structural problems such as limited human resources, lack of contextual strengthening of Dhamma values, and an institutional image that is not yet strong in society. This study uses a library research method with content analysis and hermeneutics techniques to explore the relevance of Buddhist teachings to the dynamics of modern education. In the context of the Merdeka Belajar policy, Buddhist education has a great opportunity to transform through a flexible learning approach, strengthening student character, integrating spiritual values, and improving education management. In addition, the implementation of Buddhist leadership principles such as the Dasa Raja Dhamma and meditation practices can be a distinctive force that distinguishes Buddhist schools from other institutions. This transformation requires the active role of teachers, principals, foundations, and Buddhist organizations to synergize in building meaningful and competitive education in the digital era.